2020
DOI: 10.1038/s41467-020-19350-3
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of prospermatogonial specification in vitro from human induced pluripotent stem cells

Abstract: Establishment of spermatogonia throughout the fetal and postnatal period is essential for production of spermatozoa and male fertility. Here, we establish a protocol for in vitro reconstitution of human prospermatogonial specification whereby human primordial germ cell (PGC)-like cells differentiated from human induced pluripotent stem cells are further induced into M-prospermatogonia-like cells and T1 prospermatogonia-like cells (T1LCs) using long-term cultured xenogeneic reconstituted testes. Single cell RNA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
134
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(142 citation statements)
references
References 70 publications
7
134
1
Order By: Relevance
“…Accordingly, hPSCs are induced into cells bearing properties similar to human primordial germ cells (hPGCs) ( 8 , 9 ), the founding population of the human germ-cell lineage that eventually gives rise to either spermatozoa or oocytes. The induced hPGC-like cells (hPGCLCs) are further differentiated into oogonia/early oocyte-like cells with appropriate epigenetic reprogramming in a reconstituted ovary culture ( 10 , 11 ), or into pro-spermatogonia-like cells in a reconstituted testis culture ( 12 ). Although further reconstitution of human germ-cell development remains a key challenge, these advances recapitulate a period of more than 10 wk of human germ-cell development, leading to a number of key findings with regard to the mechanism of human germ-cell development in general, and germ-cell specification in particular ( 8 , 9 , 13 , 14 , 15 , 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, hPSCs are induced into cells bearing properties similar to human primordial germ cells (hPGCs) ( 8 , 9 ), the founding population of the human germ-cell lineage that eventually gives rise to either spermatozoa or oocytes. The induced hPGC-like cells (hPGCLCs) are further differentiated into oogonia/early oocyte-like cells with appropriate epigenetic reprogramming in a reconstituted ovary culture ( 10 , 11 ), or into pro-spermatogonia-like cells in a reconstituted testis culture ( 12 ). Although further reconstitution of human germ-cell development remains a key challenge, these advances recapitulate a period of more than 10 wk of human germ-cell development, leading to a number of key findings with regard to the mechanism of human germ-cell development in general, and germ-cell specification in particular ( 8 , 9 , 13 , 14 , 15 , 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…To characterize the transcriptome similarity between PGCs and naïve pluripotent cells, we compared the transcriptome signatures of in vitro -derived human PGCs (PGC-like cells; PGCLCs) and naïve embryonic stem cells (ESCs). We analyzed single-cell RNA sequencing (scRNA-Seq) datasets for in vitro -derived human male germ cells [Hwang et al ( 7 )] and for naïve and primed ESCs [Messmer et al ( 27 )] ( Fig. 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…The Hwang et al dataset contains information for germ cells that were sequentially differentiated from primed iPSCs: incipient mesoderm-like cells (iMeLCs), PGCLCs, multiplying prospermatogonia-like cells (MLCs), and mitotically quiescent T1 prospermatogonia-like cells (T1LCs), which are formed via transitional cells (TCs) ( Fig. 1A ) ( 7 ). Dimension reduction analysis suggested that the global transcriptome is highly similar between PGCLCs and naïve ESCs, consistent with previous reports ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations